1997
DOI: 10.1021/ja961817o
|View full text |Cite
|
Sign up to set email alerts
|

The Slipping Approach to Self-Assembling [n]Rotaxanes

Abstract: A synthetic approachsnamely slippagesto self-assembling [n]rotaxanes incorporating π-electron deficient bipyridinium-based dumbbell-shaped components and π-electron-rich hydroquinone-and/or dioxynaphthalene-based macrocyclic polyether components has been developed. The kinetics of rotaxane formation by the slipping procedure were investigated by absorption UV-visible and 1 H-NMR spectroscopies in a range of temperatures and solvents, varying systematically the size of both the stoppers and the macrocyclic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 18 publications
7
96
0
Order By: Relevance
“…As in any structural system, failure will occur at the weakest point. Published reports indicate that this ruptured 74-nN mechanical barrier is considerably weaker than any of the covalent bonds in the system, revealing that the failure occurs as the ring passes over the stopper, a process referred to as ''deslipping'' (24). To our knowledge, all experimental and theoretical data at comparable experimental conditions indicate that the rupture of any covalent bond requires Ͼ1 nN (see Table 2).…”
Section: Resultsmentioning
confidence: 81%
“…As in any structural system, failure will occur at the weakest point. Published reports indicate that this ruptured 74-nN mechanical barrier is considerably weaker than any of the covalent bonds in the system, revealing that the failure occurs as the ring passes over the stopper, a process referred to as ''deslipping'' (24). To our knowledge, all experimental and theoretical data at comparable experimental conditions indicate that the rupture of any covalent bond requires Ͼ1 nN (see Table 2).…”
Section: Resultsmentioning
confidence: 81%
“…The so-called slippage approach has been employed successfully, in the past three decades to self-assemble a series of linear [135][136][137][138][139] and branched [n]rotaxanes [140][141][142] under thermodynamic control. In this strategy, the macrocycle and the dumbbell, which are synthesized independently prior to self-assembly, are usually heated together in an appropriate solvent until the macrocycle slips over the dumbbell's stopper by overcoming the associated free energy of activation.…”
Section: Synthesis Of Interlocked Molecules By Slippagementioning
confidence: 99%
“…Recently, the Stoddart group has demonstrated [135][136] the efficiency of the slippage approach by self-assembling a number of linear and branched [2]-, [3]-, and [4]rotaxanes, incorporating p-electron-rich hydroquinone-based macrocyclic polyethers and p-electron-deficient bipyridinium-based dumbbellshaped compounds.A kinetic investigation of the slippage process revealed [138,145] that the free energies of activation associated with the slipping-on and slipping-off processes are correlated with the size of the cavity of the macrocyclic component, as well as with the size of the stoppers attached to the dumbbellshaped component. The free energy of activation was observed to increase upon reducing the size of the cavity of the macrocycle and/or enlarging the bulk of the stoppers.…”
Section: Synthesis Of Interlocked Molecules By Slippagementioning
confidence: 99%
See 1 more Smart Citation
“…[9] Subsequent kinetic studies revealed that the size of both the macrocycle and stoppers of the axle affect the rates of slippage. [9][10][11] A number of groups have since exploited slippage to synthesise rotaxanes. [12] One of the inherent problems of rotaxane synthesis by using the slippage strategy, however, is the question of whether the resulting slippage species is a true rotaxane or a pseudorotaxane with some rotaxane character; rotaxanes are kinetically stable, whereas pseudorotaxanes can dissociate into the macrocycle and axle components, for example when dissolved in polar solvents.…”
Section: Introductionmentioning
confidence: 99%